HCCI and CAI engines for the automotive industry - Zhao, Hua (CRC Press Woodhead Pub., 2007)
Homogeneous charge compression ignition (HCCI)/controlled auto-ignition (CAI) has emerged as one of the most promising engine technologies with the potential to combine fuel efficiency and improved emissions performance, offering reduced nitrous oxides and particulate matter alongside efficiency comparable with modern diesel engines. Despite the considerable advantages, its operational range is rather limited and controlling the combustion (timing of ignition and rate of energy release) is still an area of on-going research. Commercial applications are, however, close to reality. HCCI and CAI engines for the automotive industry presents the state-of-the-art in research and development on an international basis, as a one-stop reference work. The background to the development of HCCI / CAI engine technology is described. Basic principles, the technologies and their potential applications, strengths and weaknesses, as well as likely future trends and sources of further information are reviewed in the areas of gasoline HCCI / CAI engines; diesel HCCI engines; HCCI / CAI engines with alternative fuels; and advanced modelling and experimental techniques. The book provides an invaluable source of information for scientific researchers, R & D engineers and managers in the automotive engineering industry worldwide. Presents the state-of-the-art in research and development on an international basisAn invaluable source of information for scientific researchers, R & D engineers and managers in the automotive engineering industry worldwideLooks at one of the most promising engine technologies around
Includes bibliographical references and index
Keywords: TRANSPORTATION / Automotive / Pictorial; TECHNOLOGY & ENGINEERING / Automotive; Internal combustion engines / Ignition; Internal combustion engines -- Ignition; HCCI; Verbrennungskraftmaschine; Verbrennungsmotor; Kraftfahrzeugmotor